Gene expression analysis of metabolic markers during bone regeneration in a rat model - Jonitz-Heincke, A.; Kasch, C.; Osterberg, A.; Granitzka, Thordis; Lindner, T.; Haenle, M.; Bader, R.; Skripitz, R. (Osteologie, 2014)
The RANK/RANKL/OPG system plays an important role in the regulation of bone metabolism and bony integration around implants. The aim of this study was to analyse gene expression of OPG, RANK, and RANKL in regenerating bone during implant integration. Additionally, the effect of intermittent para - thyroid hormone (PTH) treatment was analysed. A titanium chamber was implanted in the proximal tibiae of 48 female rats. The animals received either human PTH or saline solution (NaCl). After 21 and 42 days, RNA was isolated from tissue adjacent to the implant and expression of RANK, RANKL, and OPG was analysed. After 21 days, very low expression levels of all genes were shown. In contrast, increased gene expression after 42 days was determined. Expression of RANK and RANKL was lower than that for OPG. The lower expression levels after 21 days might be due to still ossifying, fibrotic tissue around the titanium chamber. An increased OPG synthesis rate associated with decreased RANKL expression after 42 days revealed bone-forming processes. Despite significant differences in gene expression between the time points, only slight differences were observed between application of intermittent PTH and NaCl after a period of 42 days.
Keywords: Bone regeneration; OPG/RANK/RANKL system; gene expression; animal model